Assessing the pattern between customer metrics and net promoter score : a portuguese insurance sector case study - Santos, Diogo Alexandre da Silva (2019)
Dissertation presented as partial requirement for obtaining the Master’s degree in Information Management, with a specialization in Marketing Research and CRM